Assessing the barriers in implementing sustainable supply chain management practices: An ISM approach - Sanatan Ratna, B Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Sustainable supply chains are being adopted by the firms throughout the world due to its several advantages over the traditional supply chains. Sustainable supply chains help in tackling the environmental concerns by considering the factors affecting the environment. However detailed studies suggest that lot of medium and small-scale enterprises (SMEs) still overlook the sustainability over the economic aspect. The reason for this neglect is the existence of several barriers. Also, the enablers have not been implemented successfully. The current research work aims at identifying these barriers for a Nickle plating SME and analysing them by using an integrated approach Interpretive Structural Modelling (ISM). Here, nine environmental barriers have been identified with the help of expert opinion and literature review. The nine barriers under consideration are, Lethargy of top management, Unsupportive government policies, Technical inability, improper human resource utilization, Poor IT support, Society Unawareness, Poor environmental steps, Issues within organisation & Fear of risk involved. A Structural framework has been drawn with the use of Interpretive Structural Modelling (ISM) technique, to understand the inter-relationship among the nine identified barriers to find the reliance of one on another. Moreover, the ISM results are further classified based on driving and dependence power. The partitioning of levels for Barriers helps in identifying the most critical barrier among all others.